INNOVATIVE APPROACHES TO THE DEVELOPMENT OF PERSONALITY AND FORMING CHILD’S BEHAVIOR IN PEDAGOGICAL HERITAGE OF C. FREINET - Goncharenko-Zakrevska, Natalia (Educological discourse, 2017)
The article examines the original pedagogical concept of the French teacher-practitioner of the twentieth century, Celesten Freinet, concerning the labor education of a child at school. Detailed consideration is given of the theoretical positions on which C. Freinet emphasizes in his system, revealing his special understanding of the nature and development of the child, on the dynamical and genetic approach to solving the problem of human development, the crucial role of needs, instincts, aspirations and desires of children in cognitive activities and development. The psychological foundations of the mechanism of personality development and formation of the child’s behavior are considered; the role of games and work in the life of the child and activization of activities, the need of children in verbal and practical self-expression, the socialization of children in school. It is noted that adaptation of the child to social conditions at school should ensure its readiness for real life in society. Organization of education and activity training on a democratic basis of cooperation is the core of C. Freinet’s pedagogy, which implements a set of methods aimed at achieving the humane goal of education and training, namely the disclosure of the child’s individuality and the free development of the individual. It emphasizes the educational significance of material support and modern technical means that should become obligatory means of learning and cognitive activity of students in the modern democratic school. C. Freinet offers to remove the game from the educational process and introduce labor and “labour-game” as a functional game that satisfies children’s interests. The need for the organization of the educational environment, thus, in the pedagogy C. Freinet comes not only from the understanding of its importance for the development of the child, as with other educators, but above all, from the understanding of the individuality of this development.